Emergence of autochthonous Leishmania infantum infection in dogs from Costa Rica confirmed by multimodal diagnostics: a case series - Montenegro, Víctor M.; Cajal-Omella, Leticia; Campos-Camacho, Josué; Jiménez-Tuk, Javier; Mata-Somarribas, Carlos; Alfaro-Alarcón, Alejandro; Guevara-González, Mariana; Peña, Paula; Quesada, Joban; Romero-Vega, Luis M.; Rojas, Alicia (Frontiers in Veterinary Science, 2026)
BackgroundCanine visceral leishmaniasis (CVL) is a vector-borne zoonotic disease caused by Leishmania infantum. This parasite has been reported in humans and dogs from Costa Rica over the past four decades as sporadic reports. In this study, we analyzed eight cases of autochthonous infections in dogs presumably originating from Santa Cruz, Guanacaste, and Santa Ana, San José, Costa Rica, none of which had a history of travel abroad.MethodsEight dogs with suspected CVL were analyzed using serological assays (Speed Leish K® (VIRBAC Diagnostics, France) or Antigen Rapid CaniV-4 (Leish)® (BIONOTE, Mexico)), five dogs were detected in 2023, and three during 2025. Histopathological staining was applied in cases with spleen, dermal, and lymph node involvement to determine the presence of Leishmania amastigotes. Blood, lymph node aspirates, conjunctival swabs, or cutaneous lesion swabs were also analyzed for the presence of Leishmania spp. ITS1, hsp70, and kDNA fragments. Phylogenetic and haplotype network analyses were conducted for hsp70 and kDNA data.ResultsFour dogs showed various clinical manifestations that included persistent anemia, thrombocytopenia, splenomegaly, exfoliative dermatitis, and onychogryphosis, whereas the other four dogs remained subclinical or asymptomatic. Histopathological analysis revealed numerous intracellular amastigotes in lymph node aspirates, spleen sections, and ear skin biopsy. Moreover, seven out of eight dogs were positive in the serological analysis, and the other seven to the Leishmania ITS1 PCR. Phylogenetic analysis of kDNA fragments revealed that sequences derived from our country clustered with those of L. infantum from the Old World, rather than with ones from Brazil, indicating a likely introduction from outside the Americas. All infected dogs received allopurinol and, when available, also meglumine antimoniate.ConclusionInfection with L. infantum in Costa Rican dogs was confirmed by clinical and laboratory evidence and thus represents the first autochthonous cases of CVL in our country. This study highlights the urgent need for routine canine testing, sandfly surveillance, access to proper treatments, and increased awareness, emphasizing the importance of public health policies for controlling leishmaniasis in both animals and humans from a One Health perspective.